The relationship between linguistic prejudice and the approach to teaching the portuguese language in basic education - Balbi , Edma Regina Peixoto Barreto Caiafa; Soares , Kathia Vívian Machado dos Santos; Luquetti , Eliana Crispim France (Seven Editora, 2023)
According to the concepts of Linguistics and Sociolinguistics and having as a starting point the myths around linguistic prejudice, the present paper aims to demystify this concept and search for a way to diminish the abyss between the spoken language and the one taught in classrooms. Taking the National Curricular Parameters (Parâmetros Curriculares Nacionais – PCNs) and the Common National Curricular Basis (Base Nacional Comum Curricular – BNCC) guidelines as a documentary basis and, as a discussion basis, observations of the empiric reality arising from teaching practice in basic education classrooms of public schools, it seeks to balance the Portuguese language standard norm teaching approach to the linguistic variations present in spoken language, so that all students understand the different possibilities to use the language and can adequate it to the communicational context. DOI:https://doi.org/10.56238/alookdevelopv1-139